GERAKAN SOSIAL RUMAH SEHAT DAN IMUNISASI BCG SEBAGAI LANGKAH MENURUNKAN KEJADIAN TUBERKULOSIS (TB) ANAK - Mardotillah, Mila; Soemarwoto, Rini Susetyawati; Sugandhi, Yogi Suprayogi (HUMANIKA, 2018)
In an effort preventive and promotion to improve health degree, individuals and families must understand the concept of sick and healthy. Understanding of the concept can help everyone in maintaining their health with the help of medical and social surroundings. Social assistance is an environment which a child grows and develops. Social support in creating a healthy home conditions and the implementation of BCG immunization is necessary condition of the child in an effort to prevent child’s TB disease. Child’s life would be a lot of spent time at home, so parents need to understand how healthy housing conditions as well as the support of family health also immunization status that must be met by parents for a child's rights in obtaining proper health status. Healthy homes and BCG immunization is an effort to reduce the number of child’s TB. The role and knowledge of parents to the importance of these two things is major key to the success of child’s TB treatment in terms of preventive and health promotion role very valuable in enhancing parents knowledgeable on child TB incidence. Support for social groups that formed in the communities through the role of cadres, religious figures, community figures and officials is important things for the successful of children tuberculosis treatment through healthy housing conditions and BCG immunization.